Studying and employing the 2020 seminar “strengthening the national unity bloc, building a clean and strong party as well as a transparent political system based on Ho Chi Minh’s ideology, morality and style” in practice - Lê Tố Anh (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Continuing implementation of Directive 05-CT/TW of the Politburo of 15 May 2016 on learning and following Ho Chi Minh’s ideology, morality and style; the Central propaganda and training commission enacts the 108-HD/BTGTW instruction about topic of 2020 seminar: “Strengthening the national unity bloc, building a clean and strong party as well as a transparent political system based on Ho Chi Minh’s ideology, morality and style”.  Studying this year’s seminar is to broadening the knowledge of student about the enormous role of NUB, the content of implement NUB method according to Ho Chi Minh’s ideology; Thence, applying to work life of each person, especially to buid a clean and strong party, a transparent political system. From the learning purpose, content of the seminar, the author states 7 connections in studying and following Ho Chi Minh's ideology, morality and style on “Strengthening the national unity bloc, building a clean and strong party as well as a transparent political system based on Ho Chi Minh’s ideology, morality and style” in practice.